Making a Website Company Profile as a Promotional Media Using CMS Wordpress at MAB Screen Printing in Jember City - Mario Daniar Nur Prastyo; Fatkhur Rochman; Joni Dwi Pribadi (Manajemen Bisnis, 2025)
In the digital era, business competition had become increasingly intense, pushing companies to adopt more effective and innovative promotional strategies. Many small and medium enterprises, including MAB Screen Printing in Jember, still relied on conventional promotional methods that often failed to reach a broader audience. To adapt to the evolving digital landscape, the use of technology particularly a website was seen as a vital step in expanding market visibility. In response to this need, a company profile website was developed for MAB Screen Printing using the WordPress content management system. This effort aimed not only to modernize the company's promotional approach but also to test how effective the website would be as a digital marketing tool amidst current challenges. To ensure that the analysis of the website delivered both function and impact, input was gathered from web development professionals, marketing experts, and a group of customers. Their feedback helped evaluate key aspects such as user experience, content clarity, and service interaction offered through the website. The final evaluation of this study showed that the website had met high standards of quality and effectiveness. It was positively received by both experts and users, confirming its strength as a promotional medium. Recommendations were made for the company to continue developing the website and make the most of its features to support future digital growth.